Dynamics of CO2 Emissions in Emerging Markets: Evidence from BRICs, MINTs and Iran over 1990-2011 - Rüstemoğlu, Hasan (Eastern Mediterranean University EMU - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
Human induced environmental impacts were started more than 10000 years ago with the agricultural revolution. However, after beginning of the industrial revolution which was almost 200 years ago, the most destructive human impacts have begun to be observed. Together with the industrialization, rapid population growth, huge energy demand, the unavoidable human impacts on the earth were started. The most important one is the climate change and global warming. During the 20th century, many evidences of global warming were proved by the scientists. Accelerating concentrations of the greenhouse gases (GHGs) – more specifically the increasing amount of carbon dioxide (CO2) emissions – in atmosphere are accepted as the main causes of climate change. Developed and developing countries have two different perspectives about the global warming. Developed countries suggest the immediate solution of the problem, by implementing the necessary energy and environment related policies to reduce the CO2 emissions and then stop the climate problem. However, developing countries firstly aim to accomplish their development and then to treat the environmental issues. Regarding developing countries, environmental issues have also become a certain problem starting from 1980s. The water and air quality in developing countries is worse than the developed countries nowadays which also create health issues in addition to environmental problems. Carbon dioxide (CO2) has the greatest share among greenhouse gases (GHGs) and it is widely accepted as the main reason of climate change and global warming. Therefore, this study firstly aims to decompose the CO2 emissions (which are the most important reason of the greatest environmental problem) in BRICs (Brazil, Russia, India, and China) and in MINTs (Mexico, Indonesia, Nigeria, and Turkey) from 1990 to 2011 to see the effects of different factors on CO2 emissions. A decomposition method which is called the refined Laspeyres index method (suggested by Sun in 1998) was utilized and the impacts of four main factors including economic activity, energy intensity, population effect, and carbon intensity have been considered. In addition, as a case study, Iran’s CO2 emissions have also decomposed for the same period to identify the factors that are affecting them. For Iran, both refined Laspeyres index method and logarithmic mean Divisia index methods were utilized to analyze the factor changing CO2 emissions and to provide a comparison between these methods. Empirical findings reveal that each of these factors has different impacts on each country’s carbon emissions. As a third aim, the decoupling factor that is suggested by OECD was calculated and the existence of decoupling between economic growth and environmental pollution was tested for every research country. Finally, different policy suggestions for each country have been provided. Keywords: CO2 emissions, global warming, BRICs, MINTs, decomposition analysis, refined Laspeyres index method, logarithmic mean Divisia index method, Iran

ÖZ: İnsan kaynaklı çevresel etkilerin ortaya çıkışı günümüzden 10000 yıl kadar öncesine, tarım devrimine kadar dayanmaktadır. Lakin en yıkıcı insan kaynaklı çevresel etkilerin ortaya çıkması ise daha yakın bir tarihe, 200 yıl kadar önceki sanayi devrimine işaret etmektedir. Sanayileşme ile birlikte hızlı nüfus artışı, yüksek enerji tüketimi ve şehirleşme gibi faktörlerin bir araya gelmesi neticesinde geri dönüşü olmayan insan kaynaklı çevresel etkiler ortaya çıkmıştır. Bu çevresel sorunların en önde geleni iklim değişikliği ve küresel ısınmadır. Yirminci yüzyıl boyunca küresel ısınmanın çeşitli kanıtları, çeşitli bilim insanları tarafından ispatlanmıştır. İklim değişikliğinin temel sebebi olarak da atmosferde yoğunluğu artan sera gazları – özellikle karbon dioksit gazının miktarındaki artış – gösterilmektedir. Gelişmekte olan ülkeler ve gelişmiş ülkeler bu çevresel soruna farklı bakış açılarıyla yaklaşmaktadır. Ekonomik kalkınmasını tamamlamış olan gelişmiş ülkeler, sorunun ivedilikle, uygun enerji ve çevre politikalarıyla çözümünü önerirken, gelişmekte olan ülkeler ilk olarak ekonomik kalkınmayı tamamla sonra çevreyi düzelt felsefesini benimsemişlerdir. Gelişmekte olan ülkelerdeki çevre sorunları da 1980’li yıllardan itibaren hissedilir düzeyde artış göstermektedir. Bu ülkelerdeki hava ve su kalitesi gelişmiş ülkelere kıyasla ciddi oranda düşüktür ve bu durum beraberinde çevresel sorunların yanı sıra sağlık sorunlarını da getirmektedir. Karbon dioksit sera gazları arasında en yüksek orana sahiptir ve iklim değişikliği ile küresel ısınmanın öne çıkan sebebi olarak kabul edilir. Bu sebeple bu çalışma, gelişmekte olan BRICs (Brezilya, Rusya, Hindistan ve Çin) ve MINTs (Meksika, Endonezya, Nijerya, Türkiye) ülkelerindeki karbon dioksit emisyonlarını (başka bir deyişle en büyük çevre sorununun arkasındaki en önemli faktörü) 1990 – 2011 dönemi için ayrıştırmayı amaçlamaktadır. Böylece farklı etkenlerin karbon dioksit emisyonlari üzerindeki etkileri de araştırılmış olunacaktır. Analiz çerçevesinde Sun (1998) tarafından önerilen rafine Laspeyres endeks ayrıştırma yöntemi kullanılmış, dört önemli faktörün (ekonomik aktivite etkisi, nüfus etkisi, enerji yoğunluğu etkisi ve karbon yoğunluğu etkisi) karbon emisyonları üzerindeki etkisi tahlil edilmiştir. BRIC ve MINT ülkelerinin yanı sıra Iran için de aynı zaman aralığında emisyon ayrıştırma analizi gerçekleştirilmiş, rafine Laspeyres endeks methoduna ek olarak logaritmik ortalı Divisia endeks methodu kullanılmıştır. Böylece karbon emisyonlarına etkiyen faktörlerin yanında iki method arasında bir karşılaştırma anlizi gerçekleştirilmiştir. Ampirik bulgular, dokuz ülke için de dört etkenin farklı derecelerdeki etkilerine dikkati çekmiştir. Çalışmada ayrıca OECD tarafından önerilen ayrışım faktörü her ülke için hesaplanmış, ekonomik büyüme ile çevresel bozulma arasında bir ilişki olup olmadığı analiz edilmiştir. Sonuç olarak her ülke için ayrı ayrı politikalar önerilmiştir. Anahtar Kelimeler: Karbon dioksit emisyonları, küresel ısınma, BRIC ülkeleri, MINT ülkeleri, ayrıştırma analizi, rafine Laspeyres endeks ayrıştırma yöntemi, logaritmik ortalı Divisia endeks yöntemi, Iran
Doctor of Philosophy in Economics. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2016. Supervisor: Prof. Dr. Sevin Uğural.
Keywords: Economics; Air Pollution-Economic aspects; Air Pollution-Carbon dioxide; Environmental policy-Economic aspects-BRIC (Brazil, Russia, India, China)-Iran; Global warming